Incrementar la confiabilidad del variador de velocidad de 1500 kw del ventilador de tiro inducido de la planta de molienda Latacunga, Holcim Ecuador S.A - Aguilar Peñaloza, Cristian Renán (2016)
Holcim Ecuador has a cement grinding plant, called Latacunga plant, one of the main processes is cement grinding, it’s denominated like the spraying process for the production of raw materials cement. This industrial plant has a vertical roller mill and a main fan as two of the most important equipment for this production process. This plant implemented the installation of a Variable Speed Drive of 1500 Kw for the operation and control of the main fan in 2003; the expected results were achieved, demonstrating a better airflow control and a significant saving of electric energy in this process. But after about two years of operation, the variable speed drive began to report failures. It provokes stops cement grinding process, sometimes reaching to out of service….